Predicting the critical drainage induced by soil seepage failure during pumping in foundation pit construction - Fuwei JIANG; Shujun TANG; Xiaofei DENG; Zhenchao LI; Fawang ZHANG; Hongyuan YIN (Shuiwen dizhi gongcheng dizhi)
In the construction of foundation pits with shallow groundwater levels, improper control of pumping strength often leads to soil penetration failure, resulting in engineering accidents, casualties, and property losses. Currently, existing research mainly focuses on soil conditions, settlement deformation prediction, construction pumping measures, etc., and rarely involves the critical pumping quantity. However, the critical pumping quantity is a key parameter for pumping safety in foundation pit construction and there is no effective method to calculate or test this parameter. Based on Darcy’s law and the equivalent infinitesimal formula, and the formula for calculating the permeability coefficient of pumping tests recommended by the specification for borehole pumping test of hydropower projects （NB/T 35103—2017）, this study deduced the expressions of critical pumping quantity of the seepage failure under four conditions, including submersible incomplete hole, submersible integral hole, confined water incomplete hole and confined water integral hole. To ensure that the calculated result is more effective, the calculated expression was modified by introducing correction coefficient. The results indicate that the relationship between the critical drawdown volume for inducing soil permeability failure in the four cases and the critical permeability velocity is linear, suggesting that measuring the critical permeability velocity of the soil at the site can determine the critical drawdown volume. In a case study of basement excavation in Hohhot, it is found that the cobble layer has the highest potential for water permeability failure. Laboratory measurements revealed a critical permeability velocity for its failure of 7.1×10−4 m/s. To prevent damage to this layer during pumping, an artesian well SJ1 with a designed critical drawdown volume of 174.45 m3/d was used, and actual pumping volumes were controlled within 150 m3/d without observing any permeability failures, demonstrating applicability of the proposed method. Therefore, compared to existing qualitative experience-based methods for predicting critical drawdown volumes in basement excavation, the quantitative calculation method holds greater practical application value.